Gestión de programas sociales de apoyo alimentario y su incidencia en el desarrollo de capacidades en sus beneficiarios de la provincia de Trujillo: 2001-2009 - Aguirre Morales, Juan Dilberto (2012)
This research originates because, poverty and extreme poverty is latent in Peru and Trujillo Province in particular, which is a negative legacy and a challenge to plan and propose solutions. In this regard, governments have developed social programs to provide food to low-income population, but they have not had adequate planning, organization or direction, so before solving the problems, in some cases they had contributed to worse. The targets proposed by the Government in the Charter of Social Policy and the Multiyear Macroeconomic Framework, no special importance is given to food and nutrition. Also, the above documents are those governing the country's social policy in the short, medium and long term in these documents, there are no precise goals and objectives, which aims to increase levels of food and nutrition that will lead to reduced levels of poverty in the country, with emphasis on the most vulnerable groups. For the development of this work we have applied the methodology, techniques and tools necessary for an adequate investigation oriented to the management of social programs and capacity building of beneficiaries. This research concludes that the food support social programs have not yet achieved its goals, objectives, institutional mission and vision, because they operate in the context of a management which prioritizes the development capacity of beneficiaries.